Pengetahuan Wanita Usia Subur Tentang Pencegahan Kanker Payudara - Rukinah Rukinah; Saniasa Luba (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Abstract. Introduction; breast cancer is the number 2 killer cancer after cervical cancer. Objectives; know the knowledge of women of childbearing age about cancer prevention. Method; The type of research used is descriptive type. Data collection used a questionnaire containing questions about the knowledge of fertile women. Data analysis using SPSS 21. Result; shows that more and more people know the meaning of breast cancer, namely 68 people (68%), risk factors for breast cancer 57 people (57%), breast cancer symptoms 64 people (64%), breast cancer prevention 74 people. (74%), and BSE (BSE) as many as 55 people (55%). Conclusion; that the understanding of breast cancer, breast cancer symptoms, breast cancer prevention and breast self-examination are included in the good category. All women deepen and expand more knowledge about breast cancer prevention.